The NPM’s Impact on Service Quality: Public Perception From Gresik Population and Civil Registration Office - Kharisma Insani Rahesty; Roekhudin; Mirna Amirya (Universitas Muhammadiyah Malang, 2025)
Purpose: This study aims to examine and analyze the impact of implementing the seven characteristics of New Public Management on the quality of public services at the Population and Civil Registration Office in Gresik Regency. Methodology/approach: This study uses a quantitative approach. The population used is the entire community of Gresik Regency who have ever received public services at the Gresik Population and Civil Registration Office. The data used is primary data obtained directly from respondents' answers to questionnaires distributed using convenience sampling techniques. The data was analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach using SmartPLS 4.1.0.0 software. Findings: This study found that Professional Management, Performance Standards and Measures, Output and Outcome Control, Work Unit Division, and Adoption of Business Sector Management Styles have an impact on the Quality of Public Services. Meanwhile, Creating Competition in the Public Sector & Discipline and Resource Savings don’t have an impact on the Quality of Public Services. Practical implications: The implementation of New Public Management needs to be carried out in an integrated and contextual manner, taking into account the readiness of resources and institutions, in order to effectively improve the quality of public services. Originality/value: This study focuses on the Population and Civil Registration Office of Gresik Regency and expands variable X into seven variables covering seven characteristics of NPM, which are tested separately. This study also combines Agency Theory and Goal Setting Theory to provide a more comprehensive understanding of the dynamics of public services.